Treatment of young patients with HNF1A mutations (HNF1A–MODY). Issue 4 (30th December 2014) - Raile, K.; Schober, E.; Konrad, K.; Thon, A.; Grulich‐Henn, J.; Meissner, T.; Wölfle, J.; Scheuing, N.; Holl, R. W.; ,
Abstract: Aim: Children and adolescents with a molecular diagnosis of HNF1A–MODY should be treated with oral sulfonylurea according to current International Society for Pediatric and Adolescent Diabetes (ISPAD) guidelines. Methods: We surveyed the German–Austrian DPV database of 50 043 people and included 114 patients with a confirmed molecular–genetic diagnosis of HNF1A mutation and diabetes onset at below age 18 years. We analysed hypoglycaemic episodes, metabolic control (HbA1c ) and other clinical variables according to treatment groups. Results: People with HNF1A–MODY were included and analysed according to treatment with insulin alone ( n  = 34), sulfonylurea ( n  = 30), meglitinides ( n  = 22) or lifestyle ( n  = 28). In those receiving any drug treatment ( n  = 86), severe hypoglycaemia did not occur with meglitinide and was highest (at 3.6 events per 100 patient‐years) with insulin. HbA1c was highest with insulin treatment (insulin = 58 mmol/mol, 7.5%; sulfonylurea = 55 mmol/mol, 7.2%; meglitinides = 52 mmol/mol, 6.9%; P  = 0.008), whereas weight (BMI SD score), serum lipids and blood pressure were not different. Conclusions: Of note, 40% of people with HNF1A–MODY and medical treatment were receiving insulin alone and thus were not being treated in line with up‐to‐date International Society for Pediatric and Adolescent Diabetes/International Diabetes Federation guidelines, despite insulin treatment being associated with worse metabolic control and the risk of hypoglycaemia. The unlicensed use of oral drugs in patients below age 18 years and adherence by both doctors and patients to the initial insulin treatment might contribute to this finding. What's new?: The current International Society for Pediatric and Adolescent Diabetes/International Diabetes Federation (ISPAD/IDF) guidelines published in 2009 suggest switching patients with profen HNF1A mutation (HNF1A–MODY) from insulin to sulfonylurea. Despite this, 40% of HNF1A patients with paediatric‐ and adolescent‐onset diabetes continued to receive insulin treatment in Germany and Austria. Insulin treatment was associated with higher HbA1c and a higher risk of hypoglycaemia.